La cultura de la ciencia: contribuciones para desarrollar competencias de pensamiento científico en un encuentro con la diversidad - Daza Rosales, Silvio Fernando; Quintanilla Gatica, Mario Roberto; Arrieta Vergara, José Rafael (Revista Científica, 2012)
The present article emphasizes on the importance and the role of the sciences, as complex human activities, in the field of applications inside the school context, keeping in mind the values of the pupil and the objectives of the school. Therefore, the importance of outlining scientific competitions, defined as integrations of knowledge, abilities, attitudes, values and responsibilities. In order to achieve a more profound view, a series of questions are made that should be kept in mind when a curriculum of sciences is build.